2018
DOI: 10.1155/2018/9623412
|View full text |Cite
|
Sign up to set email alerts
|

miR-30 Family: A Promising Regulator in Development and Disease

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that negatively regulate posttranscriptional expression of target genes. Accumulating evidences have demonstrated that the miR-30 family, as a member of microRNAs, played a crucial regulating role in the development of tissues and organs and the pathogenesis of clinical diseases, which indicated that it may be a promising regulator in development and disease. This review aims to clarify the current progress on the regulating role of miR-30 family in tissues and organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 52 publications
2
104
0
Order By: Relevance
“…The miR-30-family is located on three chromosomal regions (chromosome 1: miR-30c-1 and miR-30e; chromosome 6: miR-30c-2 and miR-30a; chromosome 8: miR-30b and miR-30d) and consists of 12 different mature miRNAs [ 25 ]. The seed sequences of the guide strands of the miR-30 family are identical ( GUAAACA ).…”
Section: Introductionmentioning
confidence: 99%
“…The miR-30-family is located on three chromosomal regions (chromosome 1: miR-30c-1 and miR-30e; chromosome 6: miR-30c-2 and miR-30a; chromosome 8: miR-30b and miR-30d) and consists of 12 different mature miRNAs [ 25 ]. The seed sequences of the guide strands of the miR-30 family are identical ( GUAAACA ).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA-21 partially promotes hepatic lipid accumulation and cancer progression by interacting with the Hbp1-p53-Srebp1c pathway, miRNA-21 also regulates triglyceride and cholesterol metabolism by targeting HMGCR in NAFLD [24,25]. Recent studies have found that the miR-30 family play an important role in adipocyte differentiation and fat synthesis [26]. A Spanish study conducted by Latorre et al showed that patients with NAFLD and obesity had lower miR-30b-5p level in the liver compared with simple obese patients, and the expression of miR-30b-5p was decreased in hepatocytes after stimulated with fatty acid in vitro [27].…”
Section: Introductionmentioning
confidence: 99%
“…miR-30 family miRNAs are tumor suppressors frequently found to be downregulated in multiple types of cancers including the cancers of lung (Kumarswamy et al, 2012;Yang et al, 2017;Mao et al, 2018). Our findings suggest that a large number of Cd-upregulated genes were targets of miR-30 family (Fig.…”
Section: Exposure Induces Snail Expressionmentioning
confidence: 62%